False
true
false
false
Mark brainliest please
Here is how we get the answer....
First, replace f(x) with y . ...
Replace every x with a y and replace every y with an x .
Solve the equation from Step 2 for y . ...
Replace y with f−1(x) f − 1 ( x ) . ...
Verify your work by checking that (f∘f−1)(x)=x ( f ∘ f − 1 ) ( x ) = x and (f−1∘f)(x)=x ( f − 1 ∘ f ) ( x ) = x are both true.
4x-3 is the answer. Hope this helps:)
Answer:
option A is correct answer
divide both sides with 2
hope it helps
You multiply 24 by 4 witch leaves you with 96 canned dog food